2022
DOI: 10.3390/biomedicines10112834
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of YAP and the Hippo Pathway in Prostate Cancer

Abstract: The Hippo pathway regulates and contributes to several hallmarks of prostate cancer (PCa). Although the elucidation of YAP function in PCa is in its infancy, emerging studies have shed light on the role of aberrant Hippo pathway signaling in PCa development and progression. YAP overexpression and nuclear localization has been linked to poor prognosis and resistance to treatment, highlighting a therapeutic potential that may suggest innovative strategies to treat cancer. This review aimed to summarize available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…The suppression of Hippo signaling is a significant factor in contributing to the aggressiveness of PCa. 22 To investigate the mechanism underlying the regulation of growth and metastasis of PCa cells by SHOX2, we initially examined alterations in the protein expression profiles of the Hippo signaling pathway in TCGA datasets. We observed a significant decrease in the levels of p-YAP-S127 (which is the phosphorylated form of YAP upon Hippo activation and secluded in the cytoplasm by binding to 14–3–3 protein), in PCa tissues exhibiting increased expression of SHOX2 as opposed to those with low levels of SHOX2 ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…The suppression of Hippo signaling is a significant factor in contributing to the aggressiveness of PCa. 22 To investigate the mechanism underlying the regulation of growth and metastasis of PCa cells by SHOX2, we initially examined alterations in the protein expression profiles of the Hippo signaling pathway in TCGA datasets. We observed a significant decrease in the levels of p-YAP-S127 (which is the phosphorylated form of YAP upon Hippo activation and secluded in the cytoplasm by binding to 14–3–3 protein), in PCa tissues exhibiting increased expression of SHOX2 as opposed to those with low levels of SHOX2 ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, numerous somatic and germline alterations have been identified in the Hippo, PI3K, and MAPK signaling pathways, indicating potential factors that contribute to disease initiation, metastasis, and castration resistance [ [29] , [30] , [31] ]. Additionally, elevated expression of the epigenetic regulator HMGA2 within the tumor microenvironment is associated with the induction of prostatic intraepithelial neoplastic lesions, presumably by enhancing paracrine Wnt signaling in adjacent prostatic epithelial cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that YAP plays an oncogene role in a variety of tumors, several inhibitors of YAP have been developed, including verteporfin, Vestigial-like 4 and the 17-mer peptide, but have not been validated in prostate cancer cells ( Salem and Hansen, 2019 ). NDR1 could phosphorylate YAP and promote its degradation in the cytoplasm in Hippo pathway ( Watt et al, 2017 ; Koinis et al, 2022 ). Our previous study has reported that NDR1 inhibited the metastasis of prostate cancer cells by suppressing epithelial-mesenchymal transition (EMT), and decreased NDR1 expression might lead to a poorer prognosis ( Yue et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%